Pests and diseases as constraints in the production and marketing of fruits in the Caribbean - Braithwaithe, C. ed. (IICA Port of SpainTT, 1986)
Identifies methods of control of pests and diseases. Examines impact of pests and diseases on marketing of fruit and discusses methods and techniques for alleviating postharvest problems in marketing of fruit. Identifies plant quarantine requirements for export of fruit within the Caribbean and to North American markets. Includes seven country papers which describe the agricultural sector/fruit subsector, fruit crop production and marketing, pest and disease control, plant quarantine aspects, and development plans relating to each country.